2023
DOI: 10.3892/etm.2023.11988
|View full text |Cite
|
Sign up to set email alerts
|

IL‑37 suppresses macrophage ferroptosis to attenuate diabetic atherosclerosis via the NRF2 pathway

Abstract: IL-37 is a newly discovered inflammatory factor. However, the protective effect and underlying mechanisms of IL-37 on atherosclerosis remain unclear. In the present study, IL-37 was used for intraperitoneal injection in diabetic ApoE -/- mice caused by streptozotocin. High glucose (HG)/ox-LDL was used to stimulate THP-1 original macrophage followed by IL-37 pretreatment in vitro . The atheromatous plaque area, oxidative stress and inflammation levels in ApoE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Significantly, IL-37 can mitigate ferroptosis-associated oxidative stress and Nrf2 inhibition. IL-37 enhances cellular viability and promotes the nuclear translocation of Nrf2 in THP-1 macrophages treated with oxLDLs ( 182 ). Long non-coding RNA lnc-MRGPRF-6:1 is another type of molecule that can contribute to foam cell ferroptosis.…”
Section: Cell Death In Atherosclerotic Plaques: Pyroptosis Necroptosi...mentioning
confidence: 99%
“…Significantly, IL-37 can mitigate ferroptosis-associated oxidative stress and Nrf2 inhibition. IL-37 enhances cellular viability and promotes the nuclear translocation of Nrf2 in THP-1 macrophages treated with oxLDLs ( 182 ). Long non-coding RNA lnc-MRGPRF-6:1 is another type of molecule that can contribute to foam cell ferroptosis.…”
Section: Cell Death In Atherosclerotic Plaques: Pyroptosis Necroptosi...mentioning
confidence: 99%
“…Iron overload and ferroptosis in macrophages accelerate AS progression (Ma et al, 2022). Research by Xu et al (Xu et al, 2023) demonstrated that inhibiting macrophage ferroptosis through the NRF2 pathway significantly delayed the development of AS. A study by Bai et al (Bai et al, 2020) showed that the inhibitor of ferroptosis ferrostatin-1 could alleviate AS injury in ApoE −/− mice that were fed a high-fat diet.…”
Section: Ferroptosis and Asmentioning
confidence: 99%
“… 31 High glucose (HG)/ox‑LDL stimulation and IL‑37 stimulation inhibited HG/ox‑LDL‑induced ferroptosis in macrophages, including improved cell membrane oxidation, decreased malondialdehyde expression, up-regulated glutathione peroxidase 4 (GPX4) expression and nuclear translocation of NRF2. 32 On the contrary, addition of NRF2 inhibitor suppressed effects of IL‑37 on macrophages ferroptosis. When WT mice were infected with A/California/07/2009 (H1N1) and then were injected with IL-37, expression of macrophage-related pro-inflammatory cytokines MCP-1, IL-1β, MIP-1α, MIP-1β, IFN-γ, RANTES was reduced in the lung.…”
Section: Introductionmentioning
confidence: 99%